STUDI PEMBUATAN MINUMAN PROBIOTIK DARI BUAH JAMBU AIR MANIS (Syzynum samangarense) MENGGUNAKAN Lactobacillus casei subsp. casei R-68 YANG DIISOLASI DARI DADIH - Fahrozi, Taufik Al; Pato, Usman; Yusmarini, Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to study the ratio of sweet water guava and water in making probiotic drink by using Lactobacillus casei subsp. casei     R-68 isolated from dadih. The research was carried out experimentally using a Completely Randomized Design (CRD) with tree treatments and six replications. The treatments were J1S1 (ratio of sweet water guava and water 1:0), J2S2 (ratio of sweet water guava and water 3:1), J3S3 (ratio of sweet water guava and water 2:1), J4S4(ratio of sweet water guava and water 1:1), J5S5, (ratio of sweet water guava and water 1:2) and  J6S6 (ratio of sweet water guava and water 1:3). The data obtained were analyzed statistically using ANOVA and DNMRT at level 5%. The results show that the best ratio of sweet water guava and water significantly influenced (P<0,05) the pH, total lactic acid, total lactic acid bacteria, total solid, hedonic test at taste as well as descriptive test of colour. Based on the results of this research, it is concluded that best ratio of sweet water guava and water to produce probiotic drink was 1 : 3 (J6S6) which pH 4.17, total lactic acid 0.73%, total lactic of acid bacteria 8.77 log CFU/ml, total solid 12.95% and hedonic test of colour 3.55, aroma 3.50 and taste 3.58 as well as rather prefered by panelists.Key words: probiotic drink, lactobacillus casei, guava sweet water